2020
DOI: 10.1186/s41256-020-00134-7
|View full text |Cite
|
Sign up to set email alerts
|

China-UK partnership for global health: practices and implications of the Global Health Support Programme 2012–2019

Abstract: Background: Over the past few decades, a series of major challenges to global health have successively emerged, which call for China's deeper engagement in global health governance. In this context, the China-UK Global Health Support Programme (GHSP) was launched in 2012 with about 12 million pounds funded by the United Kingdom. Objectives: The GHSP was expected to explore a new type of China-UK partnership to strengthen the cooperation in global health, and enhance China's capacity to engage in global health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…58 Also, standardizing performance thresholds to individual's characteristics, such as residents' age and socio-economic status, can improve the clinical adequacy of indicators and further reduce the impetus on physicians to game the system. [65][66][67] As the evaluation system used in Shanghai was likely influenced by the UK's QOF, [36][37][38][39] policy-makers in China should also be aware of the framework's limitations, as identified in the United Kingdom. For example, once the targets for incentive payments have been fully met, additional health gains from the QOF program become negligible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Also, standardizing performance thresholds to individual's characteristics, such as residents' age and socio-economic status, can improve the clinical adequacy of indicators and further reduce the impetus on physicians to game the system. [65][66][67] As the evaluation system used in Shanghai was likely influenced by the UK's QOF, [36][37][38][39] policy-makers in China should also be aware of the framework's limitations, as identified in the United Kingdom. For example, once the targets for incentive payments have been fully met, additional health gains from the QOF program become negligible.…”
Section: Discussionmentioning
confidence: 99%
“…These common features include the use of indicators, incentives, and weighted scoring systems (both with a sum of 1000 points) to augment family doctors' performance. This resemblance may be due to numerous Chinese articles about the QOF that were published and which included recommendations for policymakers in China to implement incentive schemes for primary care that are similar to those of the United Kingdom, [36][37][38][39] and specifically in Shanghai. 38,39 The three indicators used by the Shanghai Health Commission to measure primary diabetes care originated from China's national basic public health service standards, the first edition of which was published in 2009, and its subsequent editions.…”
Section: Introductionmentioning
confidence: 99%
“…Different stakeholders have different perceptions on this topic. International organizations and Chinese embassies emphasized China’s contribution to global health [ 8 ], while Chinese administrative agencies and professional institutes took “professional skills” for granted, believing that communication skills and limited field practices are the most challenging aspects of global health engagement [ 19 ]. This suggests that Chinese global health agencies should develop global health mindsets through global health practices and proactive integration within the global community.…”
Section: Discussionmentioning
confidence: 99%
“…The issue for deployment is not just the scarcity of health professionals but the necessary “qualified capacity” needed for global health initiatives [ 8 ]. There are limited number of training schools in China that offer professional global health courses and furthermore, the quality of training is not at par with the expectations of the international communities [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, Kwete et al [10] reviewed the research capacity of global health institutions in China, focusing on several key quantitative indicators, such as scholarly publications, research grants, faculty members, course curricula, and trainees. Other studies highlighted the opportunities and potential for global health research in China and identified several challenges [6,[11][12][13][14]. Nevertheless, evidence of the progress of Chinese universities' contributions to global health research is generally limited.…”
Section: Introductionmentioning
confidence: 99%